BRAF fusion Spitz neoplasms; clinical morphological, and genomic findings in six cases. (14th September 2020) - Kim, Daniel; Khan, Ayesha U.; Compres, Elsy V.; Zhang, Bin; Sunshine, Joel C.; Quan, Victor L.; Gerami, Pedram
Abstract: Background: Fusions involving the BRAF gene are responsible for 5% of Spitz neoplasms. To better characterize them, we report the clinical, morphological, and genomic findings of six BRAF fusion Spitz tumors. Methods: The morphological, clinical, and molecular findings of six BRAF fusion Spitz neoplasms assessed by next generation sequencing (NGS) were compared to a control set of Spitz without BRAF fusions. Results: BRAF fusion Spitz tumors had frequent predominance of epithelioid morphology (4/6 cases), frequent high‐grade nuclear atypia and pleomorphism (5/6 cases), and a frequent desmoplastic base (3/6 cases). Five of six cases were diagnosed as atypical Spitz tumor and one as Spitz nevus. All cases had uneventful clinical follow‐up. There were five different fusion partners, with CLIP2 being the most frequent. Secondary pathogenic mutations were frequent and chromosomal copy number changes were seen in three of six cases by an NGS platform. Conclusions: BRAF fusions Spitz usually have epithelioid morphology, high‐grade nuclear atypia, and desmoplasia. Chromosomal copy number changes are not infrequent. While our cases had uneventful follow‐up, a meta‐analysis of the literature suggests that among the fusion subtypes associated with Spitz tumors, they are among the subgroups more likely to develop distant metastasis.